Weapon‐related Cranial Lesions from Medieval and Renaissance Turin, Italy. (8th August 2013) - Giuffra, V.; Pejrani Baricco, L.; Subbrizio, M.; Fornaciari, G.
Abstract Archaeological excavations carried out in the square around the Cathedral of S. Giovanni in Turin brought to light burials referable to the medieval and Renaissance periods. The anthropological examination of the skeletal remains allowed to identify two skeletons from the medieval period (10th–11th centuries) and four skeletons from the Renaissance age (15th century) showing weapon‐related cranial injuries. These peri mortem lesions are indicators of interpersonal aggression and in particular of armed conflicts. The two individuals from the early medieval period presented three traumas consisting in sharp force lesions caused by bladed weapons. As regards the Renaissance sample, the majority of the nine peri mortem injuries were sharp force wounds, followed by a blunt force trauma. These distribution patterns might reflect different fighting techniques, whereas the side distribution and location of the skull trauma provide further indications on the fighting modalities. Identification of the weapons that caused these traumas is suggested. The lack of post‐cranial wounds at Piazza S. Giovanni might be explained by the greater attention paid to the head, which was the main target of attack, or by adequate protection of the body through medieval and Renaissance armours. Otherwise, the wounds in the body would have been found only in the soft tissues, with no involvement of the bones. Despite the presence of weapon injuries, the results obtained from the study of the Renaissance sample are different from the findings of other contemporary battlefields. It is highly likely that the individuals of the Renaissance age were not young soldiers employed in war episodes and brought back for burial in Turin after battles that had taken place elsewhere. Instead, they were probably individuals who had died in riots or in other violent city episodes, as the historical records for the Renaissance age seem to confirm. Copyright © 2013 John Wiley & Sons, Ltd.